Economic challenges of entrepreneurs in the Republic of Serbia operating in the most prospective economic activitiesss operations by economic sectors in the Republic of Serbia in 2018 - Aleksandra Fedajev; Danijela Voza; Marija Panić; Milica Veličković (Anali Ekonomskog fakulteta u Subotici, 2022)
High unemployment rate, low level of economic activity and low living standards are some of the most significant problems that the Republic of Serbia has been facing in the last few years. The development of small and medium enterprises and entrepreneurs as great potential to solve these problems to some extent is still not sufficiently exploited. Keeping in mind the importance of the development of this economy segment, this paper analyses the business economy of entrepreneurs by economic activities in 2018 in the Republic of Serbia to determine the economic activities that have the greatest prospects for entrepreneurship development in the future. The ratio analysis of operations was used as a starting point for comparative analysis. It was conducted using the data obtained from the Annual Bulletin of Financial Statements published by the Business Registers Agency for ten economic activities where entrepreneurs reordered the highest profitability in 2018. Using the entropy method and PROMETHEE method, the ranking of entrepreneurs according to economic activities was performed. The obtained results indicated that in 2018, the best-ranked entrepreneurs were those operating in Professional, Scientific, Innovative and Technical Activities, while the worst-ranked are entrepreneurs operating in Accommodation and Food Services.